A PROSPECTIVE OBSERVATIONAL STUDY ON HEALTH-RELATED AND MENTAL QUALITY OF LIFE ASSESSMENT IN GERIATRIC PATIENTS - Punniyakotti, Saranya; George, Samuel Gideon; Kumar, Hemanth Bhaskar; Kaliyamoorthy, Kousalya; Mustapha, Noordin Mohamed (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The objective of this study is to evaluate health-related and mental quality of life in geriatric patients and to determine the factors influencing the same. Methods: World Health Organization-BREF, EuroQoL-5D, and Mini Mental State Examination scales were used for evaluation and scoring of healthrelated and mental quality of life in geriatric patients. Logistic regression models were used to determine the predictors of health-related and mental quality of life. All statistical analyses were performed using IBM SPSS 17.0. Results: Comorbid disease conditions were found to be the significant predictor of health-related quality of life. Education and social history were predictors of cognitive function in the elderly. Conclusion: Patients in these risk line should keenly be monitored for declining health-related and mental quality of life. Disease has a significant impact on the quality of life in geriatric population. However, education, financial status, and social history were found to be the significant predictors of mental health and declining cognition. Hence, geriatric patients in the above-mentioned risk line should keenly be monitored; thereby their quality of life can be focused and improved. Keywords: Comorbidity, Geriatrics, Mental health, physical health, Quality of life.